KONSTRUKSI MODEL PERILAKU PELAYANAN KESEHATAN (CONSTRUCTION OF PUBLIC HEALTH SERVICE BEHAVIORAL MODEL) - alexsander alexsander (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
ABSTRACT Midwives as the street level bureacrats have the responsibility to overcome the problem of high rate of maternal and child mortality in Bengkulu City. The implementation of midwife duty is in dilemma due to many factors. As a result, midwifery service behavior is considered not optimal. This study aims to explore the behavior of midwives. Exploration is expected to produce a model that provides description and explanation the entity practices of Street level bureaucrats in health services delivering. Qualitative methods with case study design are used in this research. Data collection techniques are carried out with FGD, in-depth interviews, literature study and observations. The informants of the study are the midwives, patients, and multi-stakeholder. The collected data were analyzed through an inductive reasoning process, triangulation,and Vensim PLE 7.2. The study found 20 factors in three layers (service quality layer, coping behavior layer, and behavioral determinant layer) that interact with each other. Coping behavior has been moderator between service quality layer and behavioral determinat layer. Those factors contruct the unique model which simplified interaction among resources factors, personal value, and clients. The dynamic interaction shapes a behavior model of midwives in health services shows how dillematic among scarcity of resource, ambiguity and discretion blended in the routine and simplification to cope with the client needs. Some parts in the model have the possibility to be developed into strategic policy study. But before, it needs a simulation by using a variety of numerical data to test the model. Keywords: midwife, behavior, health services, dynamics system